Design and analysis of a modified segmented cladding fiber with large mode area. (February 2017) - Ma, Shaoshuo; Ning, Tigang; Li, Jing; Zheng, Jingjing; Wen, Xiaodong; Pei, Li
Abstract: This paper proposes a novel segmented cladding fiber structure for large mode area properties. In this structure a thin ring is placed between the high index core and nonuniform cladding. It is called Single-Ring Segmented-Cladding Fiber (SR-SCF). The novel fiber offers the possibility of single-mode(SM) operation from 1 µm to 1.7 µm with a large core diameter. With illustrations, the fiber has a better SM operation than segmented-cladding fiber (SCF) is demonstrated. A large effective area of 1000 µm 2 is achieved. The SM operation with very high suppression of the higher order modes can arise by 76%. Moreover, mode spacing between the adjacent modes (LP01 and LP11 ) is also improved significantly. Besides, the bending property is analyzed. It is found that the ﬁber is insensitive to bending angle ranging from −180° to 180° at bending radius of 30 cm. The proposed ﬁber will play an important role in developing high power ﬁber laser, ﬁber ampliﬁer and high power delivery application. Highlights: We model propagation properties of segmented cladding fiber and modified segmented cladding fiber. We compare two fibers on leakage loss, mode spacing and power fraction in core. Modified segmented cladding fiber has higher suppression of the higher order modes than traditional segmented cladding fiber. Effects of duty cycle, index difference, thickness and bending of modified segmented cladding fibers are discussed.